1975
DOI: 10.1007/bf00284964
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycin D effects on mitosis and chromosomes: sticky chromatids and localized lesions

Abstract: When Indian muntjac and Chinese hamster cells in culture were treated with Actinomycin D (1 micron/ml) for 1-2 hours, the sister chromatids, especially the distal segments, appeared to have difficulty separating in anaphase. The separated proximal segments progressively became stretched. The nucleolus organizer regions seemed to be most susceptible to stretching, and breaks in these regions were frequently observed. Electron microscopic observations showed that the sticky chromatids (and less frequently sticky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…3b) and found that these inhibitors were able to block transcription or translation, in line with previous studies26. Cycloheximide and actinomycin D treatments have been previously used in mitotic cell experiments where they blocked entry into S-phase, slowed mitotic progression and blocked completion of cytokinesis; however, besides that mitosis proceeded unimpaired2728293031. We found a small decrease in the number of cells in mitosis with cycloheximide (from 3.6% for untreated cells to 2.9% for 30 μM cycloheximide) as well as for actinomycin D (from 3.9% for untreated cells to 3.4% for 30 μM actinomycin D).…”
Section: Resultssupporting
confidence: 83%
“…3b) and found that these inhibitors were able to block transcription or translation, in line with previous studies26. Cycloheximide and actinomycin D treatments have been previously used in mitotic cell experiments where they blocked entry into S-phase, slowed mitotic progression and blocked completion of cytokinesis; however, besides that mitosis proceeded unimpaired2728293031. We found a small decrease in the number of cells in mitosis with cycloheximide (from 3.6% for untreated cells to 2.9% for 30 μM cycloheximide) as well as for actinomycin D (from 3.9% for untreated cells to 3.4% for 30 μM actinomycin D).…”
Section: Resultssupporting
confidence: 83%
“…As to the phenomenon of chromosomal stickness, so amply described in classical cytology (BEADLE 1932;LINDEGREN 1961) in our case the recent interpretation offered by Me GILL et al (1974) andPATHAK et al (1975) seems valid. They account for it as the failure of preprophase chromatin to condense, since the fibres are trapped in a tangle with fibres of other chromosomes.…”
Section: C) Microtubulessupporting
confidence: 72%
“…Studies conducted by many scientists [63][64][65][66][67][68] showed a preferential location of chromosome breaks induced by alquilant agents, frequently associated with heterochromatin and the defined chromosome bands. In the present study, small chromosome fragments with C-positive labeling ( Figure 4D) were observed in the A. cepa meristematic cells exposed to the two highest azo dye concentrations in the 20-h treatment.…”
Section: Bandingmentioning
confidence: 99%